OPTIMIZING MOODLE LMS FEATURES FOR FLIPPED LEARNING IN ISLAMIC EDUCATION: YOUTUBE-BASED CONTENT CURATION - Retno Aqimnad Dinana; Moh, Faizin; Abdulloh Hamid (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the optimization of Moodle LMS features in implementing flipped learning through YouTube-based content curation in Islamic Education at SMAN 17 Surabaya. The research employs a qualitative approach with a case study design, focusing on in-depth exploration of instructional practices carried out by PAI teachers. Data were collected through in-depth interviews and document analysis, and analyzed using the interactive model of Matthew B. Miles. The results showed that teachers curated YouTube videos based on material relevance, resource credibility, presentation quality, and religious moderation values ​​before integrating them into Moodle. The Activity Completion and Restrict Access features were used to organize the sequence of learning activities so that students could access the material before face-to-face learning, repeat videos when having difficulty understanding concepts, and complete prerequisite activities before participating in class discussions. During the face-to-face phase, students composed sermon texts, practiced sermons in front of the class, and took assessments through Moodle's Quiz and Assignment features. These findings indicate that Moodle functions as a pedagogical system that manages the learning flow, increases student engagement, and supports independent learning behavior. This study concludes that the effectiveness of LMS-based flipped learning depends on a pedagogical design that integrates content curation, learning activity management, and a student-centered learning experience